Rehabilitation programme to enhance community reintegration for people living with spinal cord injuries in rural areas of Limpopo Province - South Africa - Mohamed, Ehab Elsayed (My University, 2022)
Rehabilitation programmes for PLWSCI aim to give them as much independence as possible and perfect integration at a later stage. Proper rehabilitation involves effective community integration of a person with the SCI. Rehabilitation and community integration are key to return the person with an SCI to play his/her role in the community as an effective, independent, and important person. Globally, PLWSCI are facing numerous barriers and limitations, especially in rural areas, where rehabilitation resources are limited. There is a dearth of rehabilitation centres in the Limpopo Province, which might impact negatively on the rehabilitation and community integration outcomes for PLWSCI in this region. The absence of rehabilitation centres in this province point to the need for the development of extra skills for the professionals who work in the rehabilitation team in this Province. Aim and Objectives The overall aim of this study was to develop a rehabilitation programme to enhance community reintegration for PLWSCI in rural areas of the Limpopo Province, South Africa. Methodology This study used a convergent parallel mixed method design in phase 1. A mixed methodology approach consists of a set of designs and procedures in which both quantitative and qualitative data are collected, analysed, and mixed in a single study. Quantitative data were generated and collected regarding the rehabilitation and community integration challenges of PLWSCI using the Spinal Cord Injury Community Reintegration Measure (SCICRM) tool. Qualitative data were collected through focus group discussions (FGDs). In phase 2 of the study, the Delphi study design was utilised and conducted as a forecasting method based on the results of phase 1. vi Results Quantitative results show that 37% of the respondents were fully reintegrated. Moderate reintegration was above average (54.4%), while 5.7% were minimally integrated, and 3.9% failed to reintegrate into their communities. The rehabilitation teams’ home visits were further rated as “never happened” (51%) and “rarely happened” (14.3%). Patients who received a home visit from their rehabilitation team were more likely to fully reintegrate into their community, in this case, 75%. Of those who did not receive any home visits, only 39% managed to fully reintegrate into their communities. The qualitative findings, which is based on information-rich interviews with participants, indicated an urgent need for the implementation of a rehabilitation programme to enhance a successful and better community reintegration for PLWSCI. The qualitative results also highlighted the importance of home visits and following up on the patients after they have returned to their communities. The qualitative findings were presented according to six themes that were also divided into several sub-themes. In phase 2 of this study, experts agreed that the rehabilitation programme to enhance community integration for people with SCIs in the Limpopo Province should include the identification of the rehabilitation team, distribution of powers between the team members, documentation and referral letters, mobility, assistive devices, sub-acute rehabilitation tasks, home programmes, and the outcome of the successful rehabilitation. Conclusion Rehabilitation is the bridge between the SCI and successful community integration. A comprehensive rehabilitation programme implemented by a multidisciplinary team should enhance the successful reintegration of PLWSCI.
Thesis (Ph.D. (Health Sciences)) -- University of Limpopo, 2021
Keywords: Spinal cord injury; Rehabilitation; Community Reintegration; Program development People Living with Spinal Cord Injuries; Spinal cord -- Wounds and injuries; Spinal cord -- Wounds and injuries -- Patients -- Rehabilitation